An assessment of Rosendal-Mautse participation in the IDP process of Dihlabeng Municipality - Fokane, Molete Edwin (Stellenbosch : Stellenbosch University, 2008)
Thesis (MPA (School of Public Management and Planning))--Stellenbosch University, 2008.